Effects of Interval Training Under Hypoxia on the Autonomic Nervous System and Arterial and Hemorheological Function in Healthy Women - Park HY; Jung WS; Kim SW; Lim K (Dove Medical Press, 2022)
Hun-Young Park,1,2 Won-Sang Jung,2 Sung-Woo Kim,2 Kiwon Lim1- 3 1Department of Sports Medicine and Science, Graduated School, Konkuk University, Seoul, Republic of Korea; 2Physical Activity and Performance Institute (PAPI), Konkuk University, Seoul, Republic of Korea; 3Department of Physical Education, Konkuk University, Seoul, Republic of KoreaCorrespondence: Kiwon LimDepartment of Physical Education, Konkuk University, 120 Neungdong-ro, Gwangjin-gu, Seoul, 05029, Republic of Korea, Tel +82-2-450-3827, Fax +82-2-450-3949, Email exercise@konkuk.ac.krPurpose: The present study verified the effects of interval training under hypoxia, a novel exercise modality for health promotion, on the autonomic nervous system (ANS) and arterial and hemorheological function in healthy women.Methods: Twenty healthy Korean women (age: 19- 29 [24.85 ± 3.84] years) were equally assigned to interval normoxic training (INT, n = 10; residing and training under normoxia) and interval hypoxic training (IHT, n = 10; residing under normoxia and training under 526 mmHg hypobaric hypoxia) groups. All participants performed 90-min of training sessions composed of 15-min of warm-up, 60-min of interval training, and 15-min of cool-down. The interval training sessions composed of 10 repetitions of interval exercise using a treadmill (5 min of exercise corresponding to 90- 95% maximal heart rate [HR] and 1 min of rest). The training was performed 3 days per week for 6 weeks. All participants underwent body composition, HR variability, brachial-ankle pulse wave velocity, flow-mediated dilation (FMD), red blood cell (RBC) deformability and aggregation, and maximal oxygen uptake (VO2max) measurements before and after training.Results: There were no significant differences in body composition between the groups. The IHT group showed a significant improvement in the ANS function (root mean square of successive differences, high frequency, and low frequency/high frequency ratio), arterial stiffness, arterial endothelial function (FMD), hemorheological function (RBC deformability and aggregation), and aerobic performance (VO2max) compared with the INT (all p < 0.05).Conclusion: In comparison with the interval training under normoxia, the interval training under hypoxia is a novel and effective exercise modality for promoting aerobic performance with the ANS and arterial and hemorheological function in healthy women.Keywords: interval training, hypoxia, heart rate variability, arterial stiffness, arterial endothelial function, erythrocyte deformability and aggregation, maximal oxygen uptake